Saudi Healthcare Providers’ Perspectives and Clinical Practice of Anti-Obesity Medications: A National Survey - Haifa F. AlOtaibi; Sahar Alnasrallah; Assim A. Alfadda; Samar A. Alquassayer; Amr A. Arafat; Shadan AlMuhaidib; Rawabi M. Alsayer; Saleh A. Alqahtani; Waleed Alhazzani (Saudi Journal of Medicine and Medical Sciences)
Background: The rising prevalence of obesity is associated with significant health risks, underscoring the need for effective prevention and treatment. The use of anti-obesity medications (AOMs) remains limited due to several barriers. Objectives: To physicians’ perspectives and clinical practices regarding AOMs in Saudi Arabia. Methods: We conducted a national cross-sectional survey between May and August 2024 targeting family physicians, endocrinologists, and bariatric surgeons in Saudi Arabia. We distributed the survey using convenience sampling through department heads at hospitals across five regions and relevant professional societies. We collected data on clinician demographics, clinical practices, and perceptions related to AOMs. We compared responses across specialties and identified predictors of prescribing AOMs. Results: A total of 92 clinicians completed the survey: 71 family physicians, 20 endocrinologists, and 1 bariatric surgeon. Overall, 15.3% of the respondents had received formal obesity-focused training. While 92.4% reported counseling patients on obesity-related complications, 57.6% routinely referred patients to dietitians. Endocrinologists preferred international guidelines and prescribed AOMs more frequently than family physicians (90.0% vs. 60.5%; P < 0.001). Glucagon-like peptide-1 receptor agonists were the most commonly prescribed first-line agents. Key predictors of prescribing AOMs included medical specialty, guidelines preference, and prior obesity training. Conclusions: Physician specialty, clinical experience, and adherence to guidelines influence the prescription of anti-obesity medications in Saudi Arabia. Limited training and a more conservative approach among family physicians highlight the need for targeted educational interventions to improve obesity management. Initiatives should focus on harmonizing clinical guidelines and expanding access to evidence-based treatments.